1986
DOI: 10.1073/pnas.83.21.8356
|View full text |Cite
|
Sign up to set email alerts
|

Formation of muconaldehyde, an open-ring metabolite of benzene, in mouse liver microsomes: an additional pathway for toxic metabolites.

Abstract: It has been proposed that a ring-opened form may be responsible for the toxicity of benzene. The present studies demonstrate that incubation of ("C]benzene with liver microsomes (obtained from male CD-1 mice treated with benzene) in the presence of NADPH results in the formation of a ring-opened product. Evidence for the identity of this product was obtained by derivatizing with 2-thiobarbituric acid (TBA), which resulted in the formation of an adduct with a 490-nm absorbance maximum. This ''maximum is identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…5 and 6) are consistent with the data of Rushmore et al (27), who have observed different Sephadex LH-20 column proflles of dG adducts in 3H-GMP-prelabeled DNA of rabbit bone marrow mitoplasts exposed in vitro to HQ, BQ, phenol, catechol, and BT. Although phenol or other metabolites of benzene induced relatively high levels of adducts, benzene itself produced adducts at levels barely detectable by the 32P-postlabeling assay. This could result from a) less efficient conversion of benzene to phenol in the Zymbal gland cultures; b) the high volatility of benzene, reducing the effective dose reaching Zymbal glands in the culture medium; and/or c) the metabolism of benzene predominantly to a ring-opened derivative (28), which may form polar adducts not detectable by postlabeling under the (29) to generate (3 'OH)benzetheno(N1,N2)dG as the major derivative on the basis of HPLC and NMR analysis. In comparison with this data, adduct 6, which was detected as the major product of the interaction of BQ with DNA or dGp ( Analysis of AAF adducts here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6) are consistent with the data of Rushmore et al (27), who have observed different Sephadex LH-20 column proflles of dG adducts in 3H-GMP-prelabeled DNA of rabbit bone marrow mitoplasts exposed in vitro to HQ, BQ, phenol, catechol, and BT. Although phenol or other metabolites of benzene induced relatively high levels of adducts, benzene itself produced adducts at levels barely detectable by the 32P-postlabeling assay. This could result from a) less efficient conversion of benzene to phenol in the Zymbal gland cultures; b) the high volatility of benzene, reducing the effective dose reaching Zymbal glands in the culture medium; and/or c) the metabolism of benzene predominantly to a ring-opened derivative (28), which may form polar adducts not detectable by postlabeling under the (29) to generate (3 'OH)benzetheno(N1,N2)dG as the major derivative on the basis of HPLC and NMR analysis. In comparison with this data, adduct 6, which was detected as the major product of the interaction of BQ with DNA or dGp ( Analysis of AAF adducts here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Muconaldehyde was initially demonstrated to be formed in a mouse liver microsomal system supplemented with reduced nicotinamide adenine dinucleotide phosphate (NADPH) (6). A number of pathways can be postulated to lead to ringopening and the formation of muconaldehyde, as shown in Figure 2.…”
Section: Formation Of Ring-opened Metabolites Of Benzenementioning
confidence: 99%
“…The results from hydroxyl radical and singlet oxygen scavenger studies suggest that reactive oxygen species may participate in the ring-opening of benzene in the microsomal system. The formation of muconaldehyde from benzene in liver microsomes (6,21) and the finding of muconic acid in perfusate of rat liver perfused with benzene (22) suggest that the liver is a site of ring opening in vivo.…”
Section: Formation Of Ring-opened Metabolites Of Benzenementioning
confidence: 99%
“…Results from microsomal activation systems and in vivo pharmacokinetic studies have shown that the principal metabolites of benzene are phenol, hydroquinone (HQ), muconaldehyde, and catechol (CAT) (8)(9)(10). HQ and CAT accumulate in the bone marrow (11,12), where they are further activated to exert their myelotoxic effects (6).…”
Section: Introductionmentioning
confidence: 99%